Transforming the Blessed Sacrament Parishes in the Philippines through the implementation of the Liturgy of the hours as parish prayer: A multi-site case study - Dalumpines, Jaime (Animo Repository, 2006)
The popularization of the use of the Liturgy of the Hours (LOTH) as the prayer of the Christian community in the parish has been an uphill struggle and in the last decade may have hit a blank wall. However, in the Philippines the parishes administered by the Congregation of the Blessed Sacrament have for some years been using the Morning Prayer and Evening Prayer of the LOTH as parish prayer. This study wanted to examine this rather successful implementation within the framework of the MegaChange Model as expounded by William Joyce and used successfully in business organizations. In this model, change in the workforce calls for change in the organization's structure, systems and strategy in constant interaction with the former. Only four parishes under the care of the Congregation of the Blessed Sacrament were the subjects of the study: Sta. Cruz, Manila Assumption Parish in Davao City Blessed Sacrament Parish in Tigbao, Tacloban City, Leyte, and Holy Family Parish in Panal, Tabaco City, Albay. Because of the small sample, a multi-site case study was used and data gathering was done through qualitative research methods, mainly direct observation and participation and interviews. Triangulation was done through the perusal of Life 1985, and the General Statutes 1999 and the examination of the project communitaire and other archival materials at the provincialate of the congregation. Fieldwork was more extensive in Manila since it was most accessible while at least a week was spent in each of the other sites. Interviewees included the implementers of decision-makers, that is, parish priests and/or local superiors, and the parishioners who regularly attended the prayers. The goal of parish ministry is the growth of the Christian community in the life of the Spirit. The impetus for the members of the Blessed Sacrament Congregation to implement the LOTH as parish prayer is their charism: the adoration and contemplation of Jesus present in the Blessed Sacrament. This is mandatory for all its members but throughout its history they have shared this with the Christian community in the parishes and shrines they administered. Hence, they organize their clientele into fraternities and confraternities of adorers. This structure became the vehicle for bringing in the LOTH as parish prayer. Those involved closely with parish activities were empowered to take on ministerial roles as lectors, music accompanists, and others while the members of the religious community, because of their priestly and religious formation, took on the presidential roles, particularly the chanting of the psalmody during the prayers. There was little orientation and catechesis on the LOTH for the parishioners. Continuing formation for them is incorporated in the Life in the Eucharist seminars (LITES). Having prayer booklets for the people was not a problem as the Manila parish printed them, one for each week of the four-week cycle. There were no sessions for learning the psalm tones used in the chanting of the psalmody as the people were expected to learn them by singing along. Formation sessions on the Psalter and the Scriptures for the parishioners' greater appreciation and meaningful participation in the prayer remain expressed desiderata. Decision-making on aspects affecting the parish prayer life, in particular, some form of evaluation, continue to be the domain of the religious priests, Brothers and Sisters. Hence, ownership of the whole change process by the parishioners remain elusive. On the macro-level, it only takes the unilateral decision of Church leadership, whether at the parish, diocesan or national level to implement the use of the LOTH as parish prayer. But, so long as returning the prayer of the Church to the people in the pews who share the priesthood of Christ through baptism remains a perceived threat to the ministerial priesthood, the popularization of the LOTH will continue to be an uphill struggle. In the same vein, as long as the present implementation of the LOTH continues to be monastic in nature and with minimal or no inculturation whatsover, the more the LOTH remain the prayer of choice of the intellectual elite in the Christian community. In like manner, so long as the young people continue to be and to feel as outsiders and strangers to the prayer of the Church because they are not invited or made to think they have nothing to contribute, what future is there for priestly or religious vocations and the Church? Bringing back the prayer of the Church to the whole Christian community, the lay people, the religious, the priests and the bishop together, requires a convention - a new way of thinking, of doing and valuing. MegaChange in the parish can only happen when the parishioners are also subjects and not only objects of the apostolic ministry. The recommendations at the end of this study are really ACTION PLANS for those who take to heart the Lord's admonition to Peter and his closed followers in his last hours on earth: Could you not watch with me one hour? (Mt. 26.40b).